Caregiver burden and coping strategies in parents of pediatric patients with leukemia - Plasencia Ramos, Oscar; Mayo Puchoc, Nikol; Galvez Arevalo, Ricardo (Psicooncología, 2025)
Objective: To identify the relationship between coping strategies and burden in primary caregivers of pediatric leukemia patients in a Peruvian pediatric hospital. Methods: A descriptive, cross-sectional, single-center study was conducted in a pediatric hospital in Lima, Peru. The sample included primary caregivers of pediatric leukemia patients. The Brief COPE and Caregiver Burden Inventory were used. Multiple linear regression analyses were performed to examine adjusted relationships. Results: A total of 115 caregivers were included, with an average burden score of 49.5 points. Coping styles such as active coping (aβ = -3.14; p = 0.039), positive refocusing (aβ = -2.74; p = 0.002), acceptance (aβ = -2.50; p = 0.002), and self-distraction (aβ = -1.58; p = 0.048) were associated with lower caregiver burden. In contrast, denial (aβ = 2.58; p < 0.001) and self-blame (aβ = 3.04; p < 0.001) were associated with higher burden. Conclusión: Coping strategies such as active coping, positive refocusing, acceptance, and self-distraction are associated with a lower burden, while denial and self-blame are associated with a higher burden. It is recommended to replicate the study in other settings and with a longitudinal approach to obtain more robust results.